2000
DOI: 10.1128/iai.68.11.6233-6239.2000
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Gamma Interferon Transcription and Production by Nematode Excretory-Secretory Antigen during Polyclonal Stimulation of Rat Lymph Node T Cells

Abstract: Although certain helminth infections preferentially induce type 2 T-cell responses, the immunological mechanisms responsible for type 2 T-cell polarization remain unclear. In the present study, we investigated the effects of excretory-secretory (ES) antigen from the nematode Nippostrongylus brasiliensis on cytokine production by mesenteric lymph node (MLN) cells isolated from naive rats. MLN cells produced considerable levels of gamma interferon (IFN-γ) during a 72-h stimulation with concanavalin A (ConA) or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The Th2‐inducing ability of NES has also been used as an adjuvant to induce OVA‐ 20 and hen egg lysozyme‐ 18 specific IL‐4 production by T cells. In addition, NES has been described to suppress IFN‐γ production by rat lymphocytes whilst not effecting IL‐4 or IL‐10 production 21 . The model described in the current manuscript concurs with such observations where we showed that following ex vivo activation, NES‐specific CD4 + T cells produced IL‐4 and IL‐5 but not IFN‐γ.…”
Section: Discussionsupporting
confidence: 90%
“…The Th2‐inducing ability of NES has also been used as an adjuvant to induce OVA‐ 20 and hen egg lysozyme‐ 18 specific IL‐4 production by T cells. In addition, NES has been described to suppress IFN‐γ production by rat lymphocytes whilst not effecting IL‐4 or IL‐10 production 21 . The model described in the current manuscript concurs with such observations where we showed that following ex vivo activation, NES‐specific CD4 + T cells produced IL‐4 and IL‐5 but not IFN‐γ.…”
Section: Discussionsupporting
confidence: 90%
“…Nippostrongylus brasiliensis was maintained in our laboratory by serial passage in SD rats. Nippostrongylus brasiliensis ES product was prepared as described previously (13). Briefly, adult worms were incubated in phosphate‐buffered saline (PBS) (10 000 worms/15 mL) with 100 U/mL of penicillin and 100 μg/mL of streptomycin at 37°C for 24 h. The incubation medium was centrifuged at 20 000 × g for 30 min, and the supernatant was stored at −80°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, it may be triggered directly by nematode-derived molecules. N. brasiliensis excretory-secretory product (ES) contains various biologically active molecules, such as acetylcholinesterase, proteases, and a factor that suppresses gamma interferon production (2,4,12,14,20,29). In this context, it is of interest to clarify whether N. brasiliensis ES and/or worm extract (WE) contains factors that induce epithelial cell death.…”
mentioning
confidence: 99%